Integrasi Kearifan Lokal Dalam Pembelajaran Bahasa Indonesia Untuk Menumbuhkan Karakter Siswa Sekolah Dasar - Yoma Hatima (Journal of Humanities, Social Sciences, and Education, 2025)
Character building of students is the main goal of elementary education that can be achieved through various approaches, one of which is by integrating local wisdom into Indonesian language learning. This literature study aims to examine various research findings on how local wisdom can be utilized in Indonesian language learning to foster the character of elementary school students. Previous research shows that local content derived from folklore, proverbs, pantun, and oral traditions has great potential in instilling character values ​​such as honesty, responsibility, caring, and respect for diversity. Through the literature study method from various relevant national and international journals, the results of this study emphasize the importance of involving local culture in the learning process so that students are not only proficient in the language, but also have strong cultural roots and personalities. Learning that is contextual to the local culture has proven to be more meaningful and able to increase student motivation and involvement in the learning process. Therefore, the integration of local wisdom in Indonesian language learning in elementary schools is an important strategy in character education. This study recommends the development of local wisdom-based teaching materials and teacher training to be able to implement learning that is based on cultural values.